Organocatalytic Aerobic Oxidative Cleavage of Cyclic 1,2-Diketones - Gundala, Sivaji; Fagan, Claire-Louise; Delany, Eoghan G.; Connon, Stephen J. (Synlett, 2013)
The first organocatalytic aerobic oxidative cleavage of cyclic 1,2-diketones is reported. The reaction occurs in either aqueous or alcoholic media and is promoted by a simple N-heterocyclic carbene catalyst derived from a 1,2,4-triazolium ion. No strong oxidants are required. The application of the process in a one-pot synthesis of a cyclic anhydride is also possible.
Keywords: oxidation; biaryls; carboxylic acids; catalysis; esters